2012
DOI: 10.1007/s13337-012-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Interferon Regulation Element of Hepatitis B virus Genome In Vivo

Abstract: The roles of interferon regulatory element (IRE) in Hepatitis B virus (HBV) genome on inhibitory effect of interferon against HBV are controversial in vitro. This study aimed to determine the functional characterization of HBV-IRE sequence in vivo. Wild-type or IRE-mutant HBV replication-competent mice were firstly established, and mice were subquently treated with polyinosinic-polytidylin acid (polyI.C) or phosphate-buffered saline via intraperitoneal. Results showed that PolyI.C inhibited viral replication, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Therefore, these results indicate that the mutations in the HBV RT region may reduce the inhibitory effect of IFN-α on HBV replication. Furthermore, the IFN regulatory element mutant in HBV genome reduced the inhibitory effect of IFN-α on HBV replication in our mouse model of HBV replication (Motta et al, 2010;Liu et al, 2012). During IFN-α treatment, multiple mutations occurred in the HBV genome, including the viral polymerase, precore, core and the core promoter regions (Chen et al, 2003).…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, these results indicate that the mutations in the HBV RT region may reduce the inhibitory effect of IFN-α on HBV replication. Furthermore, the IFN regulatory element mutant in HBV genome reduced the inhibitory effect of IFN-α on HBV replication in our mouse model of HBV replication (Motta et al, 2010;Liu et al, 2012). During IFN-α treatment, multiple mutations occurred in the HBV genome, including the viral polymerase, precore, core and the core promoter regions (Chen et al, 2003).…”
Section: Discussionmentioning
confidence: 73%
“…For simulating an in vivo environment with relative high ZAP expression and HBV replication, HBV expression plasmid pHBV4.1 was subsquently delivered to this ZAP transgenic mouse liver via tail vein injection. Previous study had found that the HBV DNA replication intermediates in this mouse model were abundant on day 3 and 4, and disappeared on day 10 [ 29 ], thus day 3 after transfection was a widely used timepoint to evaluate the change of HBV transcription and replication levels [ 30 , 31 ]. Based on the previous research experience, the role of host ZAP against HBV transcription and replication in present study was also evaluated at this timepoint.…”
Section: Discussionmentioning
confidence: 99%
“…Related reports of using these methods demonstrate that modified silicone rubber can show better mechanical damping properties. Through the blend of hydroxyl-terminated polybutadiene [4] and polysiloxane, organic silicon and acrylates [5], silicone rubber and cis-polybutadiene rubber/ethylene-propylene-diene [6], polyurethane elastom and phenyl silicone rubber [7], polymethylvinylsiloxane and butyl rubber [8], the modified silicone rubbers had improved damping properties on a wide temperature range. By adding Reinforcing filler SiO 2 to methyl-phenyl-vinyl silicone rubber and comparing the damping and vibration isolation properties of three different rubbers, a high vibration-damping mechanism had been obtained [9].…”
Section: Introductionmentioning
confidence: 99%